Comparative Analysis of AWS EC2 and Heroku Hosting Performance on Interbank Transfer Application Using Atlantic Pedia API - Mohammad Robihul Mufid; Dimas Ivanda Fauzi; Rijal Abbad Fakhrillah; Lutfi Zadeh Filoshof; Fahrudin Tamimi; Yunia Ikawati; Agung Teguh Setyadi (ISAS, 2026)
Amazon Web Services (AWS) EC2 is a cloud computing service that offers highly flexible and customizable infrastructure, giving users complete control over specific server configurations. Heroku, on the other hand, is a platform-as-a-service (PaaS) focused on ease of use and application management, making it ideal for developers who prioritize speed and simplicity. Optimal hosting performance is crucial, especially for interbank transfer applications, which require fast response and a smooth user experience. Therefore, this study aims to compare which hosting platform is most optimal for an interbank transfer application developed using the Atlantic Pedia API. The hosting performance testing method between AWS EC2 and Heroku was conducted comprehensively using Google PageSpeed Insights. The metrics measured included performance, accessibility, best practices, and SEO for both mobile and desktop views. The analysis results show that AWS EC2 excels in the Performance metric, with a score of 97/100 for Mobile and 100/100 for Desktop. For Accessibility, both EC2 views scored 92/100, Best Practices 79/100, and SEO 91/100. Meanwhile, Heroku showed a Mobile Performance of 89/100 and Desktop 92/100, but excelled in Mobile Accessibility at 100/100, followed by Best Practices 75/100 and SEO 91/100.